Conscious And Unconscious Aspects Of Learning The Physical Skills Of Children 5-6 Years Old In Order To Promote A Healthy Lifestyle (Journal of Pedagogical Inventions and Practices, 2024)
This article covers the conscious and unconscious aspects of teaching children's physical skills in a preschool educational organization in the form of examples and games to teach and development.